A study on factors influencing purchases of houses among Bumiputera buyers / Noreen Yoep Ahmad - Yoep Ahmad, Noreen (Faculty of Business and Management, 2006)
This study examines the factors of marketing mix that influence the purchases of houses among bumiputera buyers of services offered. Specifically, the study examines the association between product (house), price, place and promotional activities with the sales volume of houses. delivering dervice quality is an essential strategy for success today. Furthermore, promotional activities are the determining key that could seal buyer's decision making. A structure questionnaire was developed and administered to a total of 50 respondents. Two types of data analysis, descriptive analysis and cross-tabulation were used for this research. The result provides support for three out of four objectives that were examined.